Comparative Analysis of Sales Results of Hydroponic Vegetable Farmers of Lettuce (Lactuca sativa L.) between Conventional Method and Facebook Marketplace in Kendari City - Rahadi, Muhammad Ma’rif; Rianse, Ilma Sarimustaqiyma; Gafarudin, Abdul (International Journal of Technology and Education Research, 2025)
This study is motivated by the differences in marketing strategies used by hydroponic farmers in selling lettuce (Lactuca sativa L.) in Kendari City. The development of digital technology has encouraged some farmers to use platforms such as Facebook Marketplace, while others still rely on conventional methods. The purpose of this research is to identify and analyze the differences in sales results between the two methods. This research employs a comparative quantitative approach with a total of 30 hydroponic farmer respondents. Data collection techniques include observation, questionnaires, documentation, and literature study. The data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test, as the normality test results indicated non-normal distribution. The results show that the average sales using the conventional method amounted to $40,677.67, which is higher than the Facebook Marketplace method at $24,777.67. The Wilcoxon test significance value was 0.002 (< 0.05), indicating a significant difference between the two sales methods. A total of 83.33% of respondents achieved higher sales results through the conventional method. Thus, the conventional method is proven to be more effective in increasing the income of hydroponic farmers in Kendari City, although Facebook Marketplace remains relevant as an alternative marketing channel in the digital era